Modes of Composition and the Durability of Style in Literature - Hoover, David L., 1949- (London : Routledge, 2020)
Modes of Composition and the Durability of Style employs the tools and methods of computational stylistics to show that style is extremely resistant to changes in how texts are produced. Addressing an array of canonical writers, including William Faulkner, Joseph Conrad, Thomas Hardy, and Henry James, along with popular contemporary writers like Stephen King and Ian McEwan, this volume presents a systematic study of changes in mode of composition and writing technologies. Computational analysis of texts produced in multiple circumstances of composition, such as dictation, handwriting, typewriting, word processing, and translation, reveals the extraordinary durability of authorial style. Modes of Composition and the Durability of Style in Literaturewill be essential for readers interested in exploring the rapidly expanding field of digital approaches to literature.
OCLC-licensed vendor bibliographic record.
Keywords: English literature -- History and criticism; American literature -- History and criticism; English language -- Style; Authorship; LITERARY CRITICISM / General